2020
DOI: 10.1016/j.vaccine.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pneumococcal meningitis clusters in Burkina Faso and implications for potential reactive vaccination

Abstract: Highlights From 2011 to 2017, Burkina Faso had 20 pneumococcal meningitis clusters of ≥ 5 cases per district/week. Clusters had a maximum weekly incidence of 7 cases and a maximum duration of 4 weeks. Most clusters occurred prior to 13-valent pneumococcal conjugate vaccine introduction. Clusters were caused by a mixture of serotypes, with serotype 1 being most common. Due to the limited cluster size and duration, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The decline registered in 2018 was most likely attributed to the mass meningitis vaccination campaign in 39 high-risk districts in the country in January 2017 [15,16]. Studies in Burkina Faso, Finland, Netherlands, and United States of America showed similar results of declines in meningitis incidence following vaccination [17,18]. Since studies show that vaccination signi cantly lowers meningitis incidence, introduction of mandatory meningitis vaccination is an intervention that can greatly reduce meningitis countrywide.…”
Section: Discussionmentioning
confidence: 99%
“…The decline registered in 2018 was most likely attributed to the mass meningitis vaccination campaign in 39 high-risk districts in the country in January 2017 [15,16]. Studies in Burkina Faso, Finland, Netherlands, and United States of America showed similar results of declines in meningitis incidence following vaccination [17,18]. Since studies show that vaccination signi cantly lowers meningitis incidence, introduction of mandatory meningitis vaccination is an intervention that can greatly reduce meningitis countrywide.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae can cause invasive infections such as meningitis and bloodstream infections in children. Its clinical mortality ranges from 11% to 60%, and 25% to 50% of the surviving children have severe neurological sequelae (12,13). Currently, the drug resistance of Streptococcus pneumoniae is becoming increasingly serious in clinical practice, and its drug resistance rate to penicillin is as high as 60%-88% (14).…”
Section: Discussionmentioning
confidence: 99%